Global Gender Inequality in Industry: A Systematic Review with Neutrosophic Analysis - Jimmy Hurtado Paspuel; Raquel Vera-Ortega; Angel M. Plaza; Bernardo Hubert Ovalle Correa (Neutrosophic Sets and Systems)
This study examines gender inequalities in the worldwide sector via a systematic review employing a neutrosophic approach, focusing on income discrepancies, workplace harassment, preventative strategies, professional hurdles, and leadership representation. The neutrosophic methodology categorizes findings into components of truth, falsehood, and indeterminacy, assessing evidence via four metrics: neutrosophic score, reliability index, certainty level, and information quality index. In accordance with PRISMA 2020 standards, 282 studies published from 2020 to 2024 were examined. The findings indicate that workplace harassment exhibits the most substantial evidence (reliability=0.828, IQI=0.496), succeeded by wage disparities (reliability=0.813, IQI=0.400), whereas prevention policies reveal the greatest uncertainty (reliability=0.696). Robust negative correlations between Truth-Indeterminacy (-0.861) and Truth-Falsity (-0.858) substantiate the analytical approach. The analysis identifies substantial research deficiencies in the efficacy of prevention policies and the representation of leadership, especially within North American contexts. These findings establish a thorough framework for comprehending the elements of gender inequality in the workplace, presenting explicit guidance for research objectives and policy measures to mitigate gender disparities in industry.